Midgut serine proteinases participate in dietary adaptations of the castor (Eri) silkworm Samia ricini Anderson transferred from Ricinus communis to an ancestral host, Ailanthus excelsa Roxb - Kashung, Sochanngam; Bhardwaj, Parul; Saikia, Mahaswetta; Mazumdar-Leighton, Sudeshna (Frontiers in Insect Science, 2023)
Dietary change influenced life history traits, nutritional utilization, and midgut serine proteinases in larvae of the domesticated, polyphagous S. ricini feeding on R. communis (common name: Castor; family Euphorbiaceae; the host plant implicated in its domestication) and larvae transferred to A. excelsa (common name: Indian Tree of heaven; family Simaroubaceae; an ancestral host of wild Samia species). Larvae feeding on R. communis (Scr diet) showed significantly higher measures for fecundity, body weight and took less time to reach pupation, in comparison to insects feeding on A. excelsa (Scai diet). Nevertheless, nutritional index for efficiency of conversion of digested matter (ECD) was similar for larvae feeding on the two plant species, suggesting physiological adaptations of S. cynthia ricini (especially older instars) to A. excelsa diet. In vitro protease assays and gelatinolytic zymograms using diagnostic substrates and protease inhibitors revealed significantly elevated levels (p≤ 0.05) of digestive trypsins that may be associated with metabolic costs influencing slow growth in larvae feeding on A. excelsa diet. RT-PCR with semi-degenerate, serine proteinase gene-specific primers; cloning and sequencing of 3' cDNA ends identified a large gene family comprising of at least 2 groups of putative chymotrypsins (Sr I and Sr II) resembling invertebrate Brachyurins/collagenases with wide substrate specificities, and 5 groups of putative trypsins (Sr III, Sr IV, Sr V, Sr VII and Sr VIII). Quantitative RT-PCR indicated that transcripts belonging to Sr I, Sr III, Sr IV and Sr V groups, especially Sr IV group (resembling Achelase I from Lonomia achelous) were expressed differentially in midguts of fourth instars reared on the two plant species. Sequence similarity indicated shared lineages with lepidopteran orthologs associated with expression in the gut, protein digestion and phytophagy. Results obtained are discussed in context of larval serine proteinases in dietary adaptations, domestication, and exploration of new host plant species for commercial rearing of S. ricini.